2014
DOI: 10.3389/fonc.2014.00301
|View full text |Cite
|
Sign up to set email alerts
|

Quality of Life and Toxicity after SBRT for Organ-Confined Prostate Cancer, a 7-Year Study

Abstract: Objectives: Stereotactic body radiation therapy (SBRT) yields excellent disease control for low- and intermediate-risk prostate cancer by delivering high doses of radiation in a small number of fractions. Our report presents a 7-year update on treatment toxicity and quality of life (QOL) from 515 patients treated with prostate SBRT.Methods: From 2006 to 2009, 515 patients with clinically localized, low-, intermediate-, and high-risk prostate cancer were treated with SBRT using Cyberknife technology. Treatment … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

4
79
1
2

Year Published

2015
2015
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 92 publications
(86 citation statements)
references
References 24 publications
(25 reference statements)
4
79
1
2
Order By: Relevance
“…Outcome data from eight SBRT studies of patients with early-stage prostate cancer with a combined patient cohort of n=2007 were included (17)(18)(19)(20)(21)(22)(23)(24). This included 1,281 low-risk, 622 intermediate-risk and 104 highrisk patients.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Outcome data from eight SBRT studies of patients with early-stage prostate cancer with a combined patient cohort of n=2007 were included (17)(18)(19)(20)(21)(22)(23)(24). This included 1,281 low-risk, 622 intermediate-risk and 104 highrisk patients.…”
Section: Resultsmentioning
confidence: 99%
“…This included 1,281 low-risk, 622 intermediate-risk and 104 highrisk patients. Rates of bPFS reported ranged from 77.1% to 100% (17)(18)(19)(20)(21)(22)(23)(24), at endpoints ranging 2-7 years post treatment.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…46 Reported rates of physician-scored toxicities, such as CTCAE and Radiation Therapy Oncology Group grade $3 toxicities, have ranged from 1% to 3%. 27,47 Thus, while acute bowel toxicity is fairly common, it is typically low grade and largely resolved by 6 months post treatment. With regards to dosimetric correlations with GI toxicity, King et al reported that bowel QOL was decreased significantly among patients in the top 25th percentile of rectal V 90% and V 100% .…”
Section: Discussionmentioning
confidence: 99%
“…28 However, the authors identified a 1.5% incidence of late grade $3 toxicity and noted that the majority of grade 2 toxicities were based on the prescription of medications rather than clinical presentation. Indeed, Katz and Kang 47 reported the incidence of late grade 2 urinary toxicity to be 9.1%. Correlations between GU toxicity and certain dosimetric parameters have also been reported.…”
Section: Discussionmentioning
confidence: 99%